Optimalisasi Proses Pembuatan Briket Arang Bambu Dengan Menggunakan Perekat Organik - Kale, Jefrianti; Rinaldi Mula, Yoslin ; Iskandar, Taufik ; Abrina Anggraini, Sinar Perbawani (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2019)
The use of bamboo biomass as a substitute fuel for oil and gas requires briquette technology.The objective to be achieved in this research is to find out the results of the optimization of thebio-briquette from the combination of organic adhesives on the heating value, the duration oftime, the ash content and the water content. The determined variables are adhesives: cow dung,molasses, and starch and with adhesive composition: 5%, 10%, and 15%. The results obtainedin this study are the highest heating value obtained in cow dung adhesive with a composition of15% which is equal to 6,635 cal/gr while the longest flame time occurs in cow dung adhesive is64.30 minutes. The optimal point is in cow dung adhesive where the moisture content of0.1970% with ash content of 0.6480% is obtained at which point the calorific value reaches6,485 cal/gr and the combustion rate is 64.30 minutes. And the conclusions obtained turned outto be that the optimal manufacture of bamboo charcoal briquettes using organic adhesivesaffects the Heat Value, the duration of flame, ash content, and water content